Guerrilla film marketing : the ultimate guide to the branding, marketing and promotion of independent films & filmmakers - Barnwell, Robert G. (Routledge, 2018)
Create an irresistible brand image and build an audience of loyal and engaged fans... Guerrilla Film Marketingtakes readers through each step of the film branding, marketing and promotional process. Tailored specifically to low-budget independent films and filmmakers, GuerrillaFilmMarketing offers practical and immediately implementable advice for marketing considerations across every stage of the film production process.Written byleading film industry professional Robert G. Barnwell, GuerrillaFilm Marketingteaches readers how to:Master the fundamentals of guerrilla branding, marketing and promotion;Create an integrated marketing plan and calendar based on realistic budgets and expectations;Develop internet and social media marketing campaigns, including engaging studio and film websites and powerful, marketing-centric IMDb listings;Assemble behind-the-scenes pictures, videos and documentaries;Produce marketing materials such as key art, posters, film teasers, trailers and electronic press kits (aka "EPKs"); andMaximize the marketing impact of events such as test screenings, premiers, film festivals and industry award ceremonies.GuerrillaFilm Marketingis filled with dozens of step-by-step instructions, checklists, tools, a glossary, templates and other resources. A downloadable eResource also includes a sample marketing plan and audit, a test screening questionnaire, and more.- Resumé vydavatel
Keywords: nezávislý film; marketing; independent film; příručky; elektronické knihy; handbooks and manuals; electronic books